Persepsi Siswa Muslim terhadap Pembinaan Keberagamaan di SMA Don Bosco Padang - Achmad, Rizki Hidayatullah; Yusuf, Muhammad (YASIN, 2025)
Although religious guidance in schools has been widely studied, research that specifically examines Muslim students’ perceptions of religious activities in non-Islam-based schools remains very limited. This study aims to explore the forms of religious activities implemented at SMA Don Bosco and to analyze Muslim students’ perceptions of these religious guidance programs. This qualitative case study involved ten Muslim students selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis to identify patterns of meaning in students’ experiences. The findings show that the school organizes six types of religious activities: a short Friday sermon at the beginning of each month, salat Dzuhur in congregation, tahfiz Al-Qur’an, recitation submission and murajaah, pesantren Ramadhan, and celebrations of Islamic holy days (perayaan hari besar Islam/PHBI). All of these activities receive positive responses from students because they provide spiritual, social, and emotional benefits, including increased discipline, sense of responsibility, and strengthening of religious character. These findings contribute to the development of habituation theory in religious education and broaden understanding of the role of non-Islam-based schools in fostering the religious development of Muslim students. The study underscores the importance of structured, participatory, and engaging religious activities in shaping students’ religious character and recommends that schools maintain and further develop varied religious guidance programs. Future research is recommended to employ triangulation methods and expand research sites to obtain a more comprehensive picture of religious guidance practices in different non-Islam-based school contexts.